National trends in use and costs of oral anticancer drugs in France: An 8‐year population‐based study. Issue 10 (3rd August 2017) - Bosco‐Lévy, Pauline; de Boissieu, Paul; Gouverneur, Amandine; Noize, Pernelle; Molimard, Mathieu; Fourrier‐Réglat, Annie; Bezin, Julien
Abstract: Purpose: During the last decade, many oral anticancer drugs (OAcDs) have been marketed, providing interesting but potentially costly pharmaceutical alternatives to intravenous treatments. This study aims to provide updated information on their use and costs. Methods: A cross‐sectional yearly repeated study was conducted from 2006 to 2014 using the representative sample of the French national health care insurance system claims database (EGB). OAcD use was described for each year, among prevalent (ie, patients with at least 1 OAcD reimbursement) and incident users (ie, patients with no OAcD reimbursement within the prior year) and according to their pharmacological classes (Hormone Therapy [HT], Cytotoxic Therapy [CT], Targeted Therapy [TT], and others). Demographic characteristics were described for both users; comorbidities and direct medical costs were described for incident users only. Results: The yearly prevalence and incidence of OAcD use, mainly represented by HT, remained stable from 2006 to 2014 (1.2%; 0.4%). Compared with users of other OAcD classes, the proportion of TT users substantially increased over the 8‐year study period (+9.3%), and TT incident users had more severe comorbidities at treatment initiation. The health expenditures were the most important in TT users with median monthly medical direct costs varying from 2995€ to 4968€ per patient between 2006 and 2014. Conclusion: With the development of new OAcDs, the TTs use reaches a wider population of patients but is responsible for increasing health expenditures.